Well-differentiated liposarcoma of the breast arising in a background of malignant phyllodes tumor in a pregnant woman: A rare case report and review of literature - Swetha Lakshmi Narla; Punitha Stephen; Ann Kurian; S Annapurneswari (Wolters Kluwer Medknow Publications, 2018)
Pure mesenchymal sarcomas and phyllodes tumor with sarcomatous differentiation of the breast are rare tumors. Primary breast sarcomas are a heterogenous group of neoplasms which include malignant fibrous histiocytoma, fibrosarcoma, angiosarcoma, leiomyosarcoma, osteosarcoma, rhabdomyosarcoma, and liposarcoma. Sarcomatous differentiation in phyllodes tumor is seen in the form of angiosarcoma, chondrosarcoma, leiomyosarcoma, osteosarcoma, rhabdomyosarcoma, and liposarcoma. Here, we report a case of a 28-year-old pregnant woman with a breast lump during her second trimester which drastically increased in size in the postpartum period. Wide local excision revealed a malignant phyllodes tumor with liposarcomatous differentiation. Later, the patient underwent completion mastectomy which showed residual tumor.